2008
DOI: 10.1021/jf800625f
|View full text |Cite
|
Sign up to set email alerts
|

Development and Fast Screening of Salbutamol Residues in Swine Serum by an Enzyme-Linked Immunosorbent Assay in Taiwan

Abstract: The analysis of salbutamol in swine serum is the more practical basis for large scale surveillance programs in Taiwan. Objectives of the study were to develop a new assay and to compare with a commercially available kit in field test screens. A simple and reliable enzyme-linked immunosorbent assay (ELISA) to monitor the presence of beta-agonist, salbutamol, in 1,358 field samples of swine serum that were collected from local meat markets was described. The method proved to be suitable and sensitive for the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 16 publications
(17 reference statements)
0
23
0
Order By: Relevance
“…To minimize matrix effects, two common routes are often taken, dilution or sample cleanup such as liquid or solid phase extraction. Our recent report has shown that the dilution of serum decreased and eliminated the matrix effect [10]. Obviously, the more the meat extract is diluted the smaller the matrix effect one would expect, but with concomitant lowering of the assay sensitivity.…”
Section: Analytical Performance Of Homemade Elisa Kitmentioning
confidence: 97%
See 3 more Smart Citations
“…To minimize matrix effects, two common routes are often taken, dilution or sample cleanup such as liquid or solid phase extraction. Our recent report has shown that the dilution of serum decreased and eliminated the matrix effect [10]. Obviously, the more the meat extract is diluted the smaller the matrix effect one would expect, but with concomitant lowering of the assay sensitivity.…”
Section: Analytical Performance Of Homemade Elisa Kitmentioning
confidence: 97%
“…The value of immunoassays for salbutamol residue analysis in a variety of matrices has been widely reported [7][8][9][10]. Effective surveillance for the illicit use of ␤-agonists requires sensitive and satisfactory analytical techniques for their detection in serum and tissues from treated animals, and even includes the animal feed detection, with strengthening management of feed resource and realizing the security limit of drug residue.…”
Section: Randox a R-biopharmmentioning
confidence: 99%
See 2 more Smart Citations
“…The ELISA was carried out using the methodology described previously [18]. One hundred microliters of anti-AMOZ polyclonal antibody (2.5 µg/ml) in a coating buffer (50 mM carbonate/bicarbonate buffer, pH 9.6) was added to each well of a split-type microtiter plate (12 strips of 8 wells each) with a µFill microplate dispenser (Bio-Tek), and incubation was performed overnight at 4°C.…”
Section: Evaluations Of Antibody Sensitivitymentioning
confidence: 99%